U.S. Congress. Senate. Committee on the Budget. Oral History Project oral history interviews - United States. Congress. Senate. Committee on the Budget
Oral history interviews documenting the establishment of the committee in 1974, its operation and organization, relations with other committees, dealing with various presidential administrations, and the federal budget process. Persons interviewed include Stephen Emmet Bell, John J. Conway, William G. Dauster, John L. Hilley, G. William Hoagland, Hazen Marshall, John T. McEvoy, Carole McGuire, and Larry J. Stein.
Committee responsible for drafting Congress's annual budget plan and monitoring action on the budget for the Federal Government. The committee has jurisdiction over the Congressional Budget Office.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bell, Stephen Emmet, -- 1944- -- Interviews; Conway, John J. -- Interviews; Dauster, William G. -- Interviews; Hilley, John L. -- Interviews; Hoagland, G. William -- Interviews; Marshall, Hazen -- Interviews; McEvoy, John T. -- Interviews; McGuire, Carole -- Interviews; Stein, Larry J. -- Interviews; Fiscal policy -- United States